2005
DOI: 10.1128/iai.73.12.8167-8178.2005
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Fur Regulation in Vibrio cholerae and the Role of Fur in Virulence

Abstract: Regulation of iron uptake and utilization is critical for bacterial growth and for prevention of iron toxicity. In many bacterial species, this regulation depends on the iron-responsive master regulator Fur. In this study we report the effects of iron and Fur on gene expression in Vibrio cholerae. We show that Fur has both positive and negative regulatory functions, and we demonstrate Fur-independent regulation of gene expression by iron. Nearly all of the known iron acquisition genes were repressed by Fur und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
197
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(209 citation statements)
references
References 81 publications
(99 reference statements)
11
197
0
1
Order By: Relevance
“…Virulence Assay in Animals-Fur has been shown to play an important role in the virulence of different pathogenic bacteria (18,38). We thus set out to determine whether Fur90 and the Fur-binding peptide aptamers affected the virulence of a pathogenic E. coli strain in an in vivo model system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virulence Assay in Animals-Fur has been shown to play an important role in the virulence of different pathogenic bacteria (18,38). We thus set out to determine whether Fur90 and the Fur-binding peptide aptamers affected the virulence of a pathogenic E. coli strain in an in vivo model system.…”
Section: Resultsmentioning
confidence: 99%
“…About 100 genes from various E. coli strains have been shown to be regulated by Fur: most are involved in iron homeostasis; others act in metabolism and oxidative, nitrosative, and acidic stress responses (14 -17). Because fur deletion mutants of different pathogenic bacteria such as Vibrio cholerae (18) and Pseudomonas aeruginosa (19) show a decreased virulence, Fur is considered as a potential target for novel antibiotic therapies. Finally Fur has been extensively studied through the use of fur ÏȘ strains, reporter genes, and fur mutants such as fur90 (H90Y) and fur51 (G51D), which were shown to negatively complement wild type fur (20).…”
mentioning
confidence: 99%
“…Expression profiles of bacteria lacking transcriptional regulators have been used successfully to broadly define genes impacted by the deleted regulator (1)(2)(3)(4). Although providing informative data, transcriptional analysis alone cannot distinguish between direct and indirect regulatory effects or identify regulated genes that may be transcriptionally silent under the test conditions.…”
mentioning
confidence: 99%
“…In Helicobacter pylori NapA plays a dual role in pathogenesis: in colonization and in protection against oxidative damage (Wang et al, 2006). As a protein that binds iron, it may thus serve as a primitive siderophore for mycoplasmas, although in previous work, napA was not transcriptionally responsive to changes in iron concentration in M. hyopneumoniae (Madsen et al, 2006b) as has been shown in other bacterial pathogens (Mey et al, 2005). The regulation of this gene may be a clear example of a mechanism M. hyopneumoniae uses to resist the host immune response by not activating neutrophils and thus decreasing the amount of oxidative radicals.…”
Section: Resultsmentioning
confidence: 67%